Patient iPSC-derived neural stem cells exhibit phenotypes in concordance with the clinical severity of mucopolysaccharidosis I. (14th August 2018) - Swaroop, Manju; Brooks, Matthew J; Gieser, Linn; Swaroop, Anand; Zheng, Wei
Abstract: Mucopolysaccharidosis type I (MPS I) is caused by deficiency of α-l -iduronidase (IDUA), a lysosomal enzyme involved in the breakdown and recycling of glycosaminoglycans (GAGs). Although enzyme replacement therapy is available, the efficacy of the treatment for neuropathic manifestations is limited. To facilitate drug discovery and model disease pathophysiology, we generated neural stem cells (NSCs) from MPS I patient-derived induced pluripotent stem cells (iPSCs). The NSCs exhibited characteristic disease phenotypes with deficiency of IDUA, accumulation of GAGs and enlargement of lysosomes, in agreement with the severity of clinical subgroups of MPS I. Transcriptome profiling of NSCs revealed 429 genes that demonstrated a more extensive change in expression in the most severe Hurler syndrome subgroup compared to the intermediate Hurler–Scheie or the least severe Scheie syndrome subgroups. Clustering and pathway analysis revealed high concordance of the severity of neurological defects with marked dysregulation of GAG biosynthesis, GAG degradation, lysosomal function and autophagy. Gene ontology (GO) analysis identified a dramatic upregulation of the autophagy pathway, especially in the Hurler syndrome subgroup. We conclude that GAG accumulation in the patient-derived cells disrupts lysosomal homeostasis, affecting multiple related cellular pathways in response to IDUA deficiency. These dysregulated processes likely lead to enhanced autophagy and progressively severe disease states. Our study provides potentially useful targets for clinical biomarker development, disease diagnosis and prognosis, and drug discovery.